Scenarios for measuring station-based impedances in a national transport model - Lissy La Paix; Karst Geurs (European Regional Science Association (ERSA), 2015)
The measures of local and regional accessibility have been developed separately, resulting on a scarcely studied connection between these two. Accessibility evaluation of land-use and transport strategies can be much improved by linkages with more understandable, and local, accessibility measures for research and policy makers. This paper develops a multimodal model to analyse a set of scenarios of chain mobility , i.e. bicycle route quality, BTM frequency and bicycle parking cost . The results reflect the effects on accessibility levels in a national transport model. A detailed bicycle network is implemented and linked to the public transport network. The effect of access and egress penalties is verified by introducing station specific penalties by mode and station type (mode-station constant). The penalties are derived from time valuations (VOT) and willingness to pay (WTP) for transport improvements. The study area covers 54 stations of the Stedenbaan corridor, within the Randstad south wing. A set of transport scenarios are simulated for both 2012 and 2030. A potential job accessibility measure was calculated with the matrices of travel times generated from each scenario. On average the largest travel time reduction is by 15% between 2012 and 2030, when a scenario of better network and connectivity takes place. The results also show the increase in train passengers due to improved bicycle access. We identified that transport measures should be station based. The strongest effects occur in medium and small station types, i.e. 3, 4 and 5. Particularly, station types 3 and 4 are more sensitive to changes in bicycle network than the rest of stations. At the same time, labour force has a strong impact on reaching high job accessibility levels per region and station areas. The job accessibility increased up to 20%. As future research, the behavioural elements of the national transport models can be enriched to produce more user-oriented results.
Keywords: 330; national transport model; train stations; job accessibility